Empowerment Gender approach - SOUICI, Ahmed; ACHI, Meriem (Social Sciences Journal, 2020)
Social relations control many of the gender-basedbehavioralnorms ,which are based on consecrating mens control over women,whichproduced the stereotypicalportrayal of the roles of both sexes, despite the lack of research on sociology of women ,however the subjectwasintrigued by the leaders and officials because of the increasingrole of moorings in society . A new science wasintroducedtha examines the social rootsthat affect womensworkthroughstudying the factorsinfluencingwomen. The genderapproach in empoweringwomen